Correlates of intended COVID-19 vaccine acceptance across time and countries: results from a series of cross-sectional surveys. Issue 8 (2nd August 2021) - Kerr, John R; Schneider, Claudia R; Recchia, Gabriel; Dryhurst, Sarah; Sahlin, Ullrika; Dufouil, Carole; Arwidson, Pierre; Freeman, Alexandra LJ; van der Linden, Sander
Abstract : Objective: Describe demographical, social and psychological correlates of willingness to receive a COVID-19 vaccine. Setting: Series of online surveys undertaken between March and October 2020. Participants: A total of 25 separate national samples (matched to country population by age and sex) in 12 different countries were recruited through online panel providers (n=25 334). Primary outcome measures: Reported willingness to receive a COVID-19 vaccination. Results: Reported willingness to receive a vaccine varied widely across samples, ranging from 63% to 88%. Multivariate logistic regression analyses reveal sex (female OR=0.59, 95% CI 0.55 to 0.64), trust in medical and scientific experts (OR=1.28, 95% CI 1.22 to 1.34) and worry about the COVID-19 virus (OR=1.47, 95% CI 1.41 to 1.53) as the strongest correlates of stated vaccine acceptance considering pooled data and the most consistent correlates across countries. In a subset of UK samples, we show that these effects are robust after controlling for attitudes towards vaccination in general. Conclusions: Our results indicate that the burden of trust largely rests on the shoulders of the scientific and medical community, with implications for how future COVID-19 vaccination information should be communicated to maximise uptake.